Feasibility of using teleradiology to improve tuberculosis screening and case management in a district hospital in Malawi - Rebecca Marie Coulborn; Isabella Panunzi; Saskia Spijker; William E Brant; Laura Triviño Duran; Cara S Kosack; Michael Mitchell Murowa (The World Health Organization, 2012)
PROBLEM: Malawi has one of the world's highest rates of human immunodeficiency virus (HIV) infection (10.6%), and southern Malawi, where Thyolo district is located, bears the highest burden in the country (14.5%). Tuberculosis, common among HIV-infected people, requires radiologic diagnosis, yet Malawi has no radiologists in public service. This hinders rapid and accurate diagnosis and increases morbidity and mortality. APPROACH: Médecins Sans Frontières, in collaboration with Malawi's Ministry of Health, implemented teleradiology in Thyolo district to assist clinical staff in radiologic image interpretation and diagnosis. LOCAL SETTING: Thyolo district's 600 000 inhabitants are mostly subsistence-level or migrant farmers living in extreme poverty. Health facilities include one public hospital and 38 primary health centres. Understaffing and the absence of a radiologist make the diagnosis of tuberculosis difficult in a population where this disease affects 66% of patients with HIV infection. RELEVANT CHANGES: From September 2010-2011, 159 images (from 158 patients) were reviewed by teleradiology. Teleradiology changed patient management in 36 cases (23.5%). Two (1.3%) of them were cases of pulmonary tuberculosis not previously suspected by clinical staff. In addition, the radiologist's review corrected the misdiagnosis of tuberculosis and averted inappropriate treatment in 16 patients (10.5%). LESSONS LEARNT: Teleradiology can improve tuberculosis diagnosis and case management, especially if criteria to identify the patients most suitable for referral are developed and the radiologist is conversant with local resources and health problems. Designating a clinical focal point for teleradiology ensures sustainability. Staff need time to adapt to a new teleradiology programme.